Răspuns :
a+b = 7811
a-b = 1895
⇒ a = 1895 + b
1895 +b +b = 7811
2b = 7811 - 1895
2b = 5916
b = 5916/2
b = 2958
a = 1895+b
a = 1895 + 2958
a = 4853
a-b = 1895
⇒ a = 1895 + b
1895 +b +b = 7811
2b = 7811 - 1895
2b = 5916
b = 5916/2
b = 2958
a = 1895+b
a = 1895 + 2958
a = 4853
a+b=7811 a=7811-b 1)
a-b=1895 a=1895+b 2) adunand 1) cu 2) 2a=7811+1895=9706
a=9706/2=4853 a=4853 b=7811-4853=2958
numerele sunt 4853 si 2958
a-b=1895 a=1895+b 2) adunand 1) cu 2) 2a=7811+1895=9706
a=9706/2=4853 a=4853 b=7811-4853=2958
numerele sunt 4853 si 2958